Pengaruh Harga Tiket Masuk Dan Publisitas Terhadap Minat Kunjungan Wisatawan Di Tjong A Fie Mansion - Noftaruli, Bety; Winata, Edi (CIVITAS: Jurnal Studi Manajemen, 2021)
The purpose of the study was to find out if there was any influence on admission prices and publicity on the interest of tourist visits at Tjong A Fie Mansion.The population of this study is tourists who visit in January 2021.This study sample amounted to 124 visitors by sampling using the technique of Non Prabability Sampling with Accidental Sampling. The results showed that the price of admission and publicity was able to explain its existence to the interests of tourists, in addition partially the price of admission had no effect and was not significant to the interest of tourist visits, while publicity was influential and significant to the interest of tourist visits. While simultaneously the price of admission and publicity is influential and significant to the interest of tourist visits at Tjong A Fie Mansion.